D antibodies in pregnant women in multiethnic Suriname: the observational RheSuN study. Issue 10 (13th July 2017) - Zonneveld, Rens; Kanhai, Humphrey H.H.; Lamers, Margriet; Brand, Anneke; Zijlmans, Wilco C.W.R.; Schonewille, Henk
Abstract : BACKGROUND: Maternal antibodies against the D antigen are the most common cause of severe hemolytic disease of the fetus and newborn (HDFN). In high‐income countries, the risk of D immunization has been reduced by routine antenatal and postpartum administration of RhIG from 13% to less than 0.5%. In less‐resourced countries, such as Suriname, red blood cell (RBC) antibody screening during pregnancy and prophylactic RhIG administration are not routine. Accurate data on D immunization risk is not available. In the RheSuN (Rhesus Surinamese Neonates) study, the prevalence and the hemolytic potential of maternal D antibodies were investigated. STUDY DESIGN AND METHODS: A multicenter cross‐sectional study in four major hospitals in Paramaribo, Suriname, covering 90% of approximately 10, 000 births yearly in Suriname. Included were D– pregnant women of various ethnicities seeking routine prenatal care and/or their newborns. RESULTS: D antibodies were detected in 19 of 214 D– pregnancies (8.9%; 95% confidence interval, 5.1%‐12.7%), in 2.0% of primigravid and 11.7% of multigravid women. The direct antiglobulin test was positive in 11 of 13 tested D+ newborns. Determination of D antibody titers and antibody‐dependent cell mediated cytotoxicity (ADCC) assay revealed three newborns at high risk for HDFN (ADCC > 50%). CONCLUSION: D immunization risk in Suriname women is comparable to the pre–anti‐D prophylaxis era in high‐income countries. Recommended is free‐of‐charge routine RBC antibody screening and prophylactic RhIG administration for women at risk for D antibody formation as part of standard of ante‐ and postnatal care.